2020
DOI: 10.3390/molecules25173953
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Packaging Films Based on Ethylene Vinyl Alcohol Copolymer (EVOH) and Caffeic Acid

Abstract: The main objective of this research activity was to design and realize active films with tunable food functional properties. In detail, caffeic acid (CA), a polyphenol with high antioxidant effect, was used as active ingredient in poly (vinyl alcohol-co-ethylene) (EVOH) films at 5 wt.% and 15 wt.% and successfully realized by means of the solvent casting process. Optical, morphological, thermal and mechanical studies were considered to define the effect of the presence of the CA component on the structural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 53 publications
(61 reference statements)
2
38
0
1
Order By: Relevance
“…This occurrence was the most visible in the case of polylactide containing starch with caffeic acid, where the melting point changed from 432 K to 425 K after incorporating this substance into polymer matrix. A similar phenomenon of an increase in melting point was observed by Francesca Luzi et al [ 46 ] after adding caffeic acid to poly(vinyl alcohol-co-ethylene) The plasticizing effect of natural phenolic acid in polymer matrix is not as strong as of typical widely used plasticizers but a proper modification of natural phenolic acids can result in obtaining desirable plasticizers dedicated to biocomposites. Such modifications were performed by Samir Kasmi et al [ 47 ], where ferulic acid derivatives were applied as plasticizers dedicated for PLA.…”
Section: Resultssupporting
confidence: 67%
“…This occurrence was the most visible in the case of polylactide containing starch with caffeic acid, where the melting point changed from 432 K to 425 K after incorporating this substance into polymer matrix. A similar phenomenon of an increase in melting point was observed by Francesca Luzi et al [ 46 ] after adding caffeic acid to poly(vinyl alcohol-co-ethylene) The plasticizing effect of natural phenolic acid in polymer matrix is not as strong as of typical widely used plasticizers but a proper modification of natural phenolic acids can result in obtaining desirable plasticizers dedicated to biocomposites. Such modifications were performed by Samir Kasmi et al [ 47 ], where ferulic acid derivatives were applied as plasticizers dedicated for PLA.…”
Section: Resultssupporting
confidence: 67%
“…In the case of the bio-HDPE film containing CA, shown in Figure 3 g,h, some flakes of the natural compound were also embedded in the green polyolefin matrix. According to Luzi et al [ 46 ], CA presents an irregular cubic crystal structure with a length distribution ranging between 5 and 50 ÎŒm. Finally, larger particles with a mineral-like aspect corresponding to QUER can be observed in Figure 3 i,j.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of PYC limits the mechanical performance of both film A and film B ( Figure 8 B). As reported in literature, the introduction of active ingredients in polymeric matrices generally modifies the tensile parameters [ 39 , 40 ]. The analysis of different systems confirmed that higher values for elastic modulus and tensile strength can be obtained, both in the case of unloaded and PYC loaded samples, for formulations based on film A.…”
Section: Resultsmentioning
confidence: 99%